Selected Phytochemical, Nutritional And Antioxidant Properties Of Fresh, Oven And Freeze-Dried Streblus asper Leaves - Ibrahim, Nor Mawarti (2014)
Streblus asper from the family Moraceae is known locally as kesinai in Malaysia. This medicinal herb is found in the northern region of peninsular Malaysia especially in Kedah and Perlis. Most studies on S. asper concentrate on the root part and stem bark. However, there is documentation on the traditional use of kesinai leaf for the treatment of urinary tract swelling, candidiasis, dysuria, diarrhoea, increase breast milk supply and as diuretic agent. In this research, phytochemical properties of S. asper leaves from various drying treatments were studied to get a suitable procedure to preserve and maintain a high quality medicinal plant without reducing its medicinal and nutritive value.